Validity and reliability of hip strength assessment using a frame-stabilized dynamometer system device - Spudic, D.; Janez, V.; Vedran, H. (Measurement in Physical Education and Exercise Science, 2023)
The purpose was to evaluate the intra- and inter-session reliability of hip isometric strength assessment using a frame-stabilized dynamometer (FSD) and to compare the results in the hip adduction (ADD) and abduction (ABD) strength assessment using handheld dynamometer (HHD). Twenty participants (24.2 [2.6] years, 69.3 [10.0] kg) underwent testing on an FSD (ADD and ABD short and long-lever, internal [IR] and external rotation [ER] tests) and using an HHD (ADD and ABD long-lever tests). Analysis revealed excellent (ICC2.k > 0.90) relative intra-set and inter-set reliability for two visits and good reliability for test-retest results (ICC2.1 0.79-0.90), regardless of the test. Among the tests, SEM and MDC were the highest for the IR and ER results. In comparison with HHD, long-lever ADD strength was higher and long-lever ABD strength was lower when measured using FSD. Although both measurements have been shown to be highly reliable, the discrepancy between the devices exists.